Spectrophotometric Determination of Valacyclovir Hydrochloride in Bulk and Pharmaceutical Formulations - PRASAD REDDY, D.V.; GURUPADAYYA, B.M.; MANOHARA, Y.N.; VIJAYA BHASKAR, V. (Asian Journal of Chemistry, 2010)
Two simple, sensitive, rapid and accurate colorimetric methods (Method A and B) have been developed for the estimation of valacyclovir hydrochloride in bulk and pharmaceutical dosage forms. Methods A and B are based on the formation of the coloured schiff's base in acidic conditions. The presence of heterocyclic amino group in valacyclovir hydrochloride enabled the use of its condensation reaction with aromatic aldehydes like p-dimethyl aminobenzaldehyde (PDAB) and vanillin. Method A is based on yellow coloured complex formation between valacyclovir hydrochloride and vanillin, which shows maximum absorbance at 428 nm. Method B is based on light yellow coloured complex formation between valacyclovir hydrochloride and PDAB, which shows maximum absorbance at 388 nm. The linearity was found to be 20-100 and 100-500 μg/mL for Method A and B, respectively. Proposed methods were validated statistically and the recovery was carried out by standard addition method.